Assessing the Poverty Impact of India's Largest Livelihood Security Programme: A Study Based on 68th Round of NSSO. (January 2017) - Dey, Sagarika
Abstract: The enactment of India's historic livelihood guarantee programme in the form of the Mahatma Gandhi National Rural Employment Guarantee Act (MNREGA) has been coterminous with a phase of rapid decline in India's rural poverty rates. This naturally motivates the question as to whether the observed decline in rural poverty can be attributed, at least partly, to efficient targeting and implementation of Mahatma Gandhi National Rural Employment Guarantee Scheme (MNREGS). This study underscores the fact that the welfare impact of anti-poverty programmes such as the MNREGS is critically dependent on whether these programmes actually reach the intended beneficiaries. Using the unit-level data from the 68th round of the NSSO survey on Employment and Unemployment, the article first investigates the possible 'capture' of the MNREGS at the national and also at the state levels and the consequent 'crowding out' of asset poor rural households. Statistical analysis of household data reveals that although at the national level, the scheme seems to be predominantly directed towards the poor, considerable variations exist among states. After correcting for confounders in treatment and control groups, the study finds that access to MNREGS employment significantly lowers the probability of a rural household of falling in the poverty trap. The article, therefore, concludes that the scheme has the potential of favourably impacting and protecting consumption standards among rural poor. Maximisation of this potential, however, would depend upon proper identification of needy households and rooting out of the pseudo-poor from the ambit of the programme.